Fibrinolysis and bleeding of unknown cause. Issue 4 (7th April 2021) - Mehic, Dino; Pabinger, Ingrid; Ay, Cihan; Gebhart, Johanna
Abstract: Patients with bleeding of unknown cause (BUC) present with a variety of mild to moderate bleeding symptoms, but no hemostatic abnormalities can be found. Hyperfibrinolysis is rarely evaluated as the underlying cause for bleeding in clinical practice, and well‐established global assays for abnormal fibrinolysis are lacking. Few patients with definitive fibrinolytic disorders, including α2‐antiplasmin deficiency, plasminogen activator inhibitor 1 deficiency, or Quebec platelet disorder, have been reported. This review aims to summarize data on established fibrinolytic disorders and to discuss assessments of fibrinolysis in prior bleeding cohorts. Furthermore, we review available global tests with the potential to measure fibrinolysis, such as turbidity fibrin clot assays and rotational thromboelastometry, and their relevance in the workup of patients with BUC. We conclude that, due to the lack of adequate global tests, hyperfibrinolysis might be an underdiagnosed cause for a bleeding disorder. The diagnosis of hyperfibrinolytic bleeding disorders would improve patient care as effective treatment with antifibrinolytic agents is available.